Evaluation of potato protein in starter pig diets - J W Smith II; B T Richert; L J Kats; K Q Owen; Robert D Goodband; Jim L Nelssen; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1994)
In two separate trials, the use of potato protein (75% CP, 5.9% lysine), as a replacement for spray-dried porcine plasma (SDPP) in Phase I and for spray-dried blood meal (SDBM) and select menhaden fish meal (SMFM) in Phase II diets (d 0 to 14 and d 7 to 28 postweaning, respectively), was evaluated. In Exp. 1, 185 weanling pigs (initially 9.7 Ib and 15.5 d of age) were blocked by weight and gender and allotted in a randomized complete block design to one of five dietary treatments. The control diet was formulated to 1.5% lysine and .42% methionine and contained 3% SDPP and 25% dried whey. The experimental diets were formulated by substituting, on an equal lysine basis, additional SDPP (2.5 or 5% added; 5.5 or 8% total) or potato protein (2.6% or 5.1%) for soybean meal (SBM) in the control diet. These diets were fed from d 0 to 14 postweaning. From d 14 to 28, all pigs were fed a common Phase II diet. During d 0 to 14 postweaning, pigs fed diets containing 5.5 or 8% SDPP had improved (P<.05) average daily gain (ADG) compared with those fed the control diet or the diet with 5.1 % potato protein. No differences were observed in ADG and average daily feed intake (ADFI) of pigs fed the diet with 2.6% potato protein compared with pigs fed the control diet or diets with additional SDPP. Feed intake was increased for pigs fed 8% SDPP and decreased for pigs fed the 5.1 % potato protein, when compared to the control group. Feed efficiency (G/F) was not affected by dietary treatment. Overall (d 0 to 28), no differences occurred in ADG, ADFI, and F/G among treatments. In Exp. 2, 270 weanling pigs (initially 13.7 lb and 20 d of age) were used. Pigs were blocked by weight and gender and assigned to each of three dietary treatments at weaning. There were 15 pigs per pen with six replicate pens per treatment. From d 0 to 7 postweaning, all pigs were fed the same diet that was formulated to 1.5% lysine and contained 10% SDPP and 25% dried whey. The Phase II experimental diets contained 10% dried whey and were formulated to 1.25% lysine and .34% methionine. The protein sources, 2.50% SDBM, 4.8% SMFM, or 3.92% potato protein, were substituted on an equal lysine basis, with all diets containing 22.63% SBM. From d 7 to 28 postweaning, pigs fed potato protein had decreased ADG and F/G. No differences occurred between pigs fed either SDBM or SMFM. These results suggest that potato protein as a plant protein should replace these more expensive animal protein sources only in limited amounts.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Starter; Performance; Potato protein; Porcine plasma